Profitability Analysis of Backyard Poultry Farming in Kheda District of Middle Gujarat, India: Triple Cross Vs Indigenous Chicken - Mahera, Ashish B; Mishra, Snehal; Bhagora, Nikesh J; Lad, Yogesh A; Kumar, M Sathish (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Backyard poultry is an age-old practice in India, particularly in rural areas, where households raise small groups of local chickens for  family food. Though India’s poultry industry has proliferated in the previous five decades, it has primarily been limited to the commercial  poultry sector, which is concentrated in and around urban and semi-urban areas. This study aimed to determine the profitability of  backyard poultry production of triple cross and indigenous chicken in the Middle Gujarat region. A well-structured questionnaire was  used to collect data from 15 triple cross and 15 indigenous chicken farmers comprising 30 respondents in Kapadwanj Taluka of Kheda  district in Middle Gujarat. The data were analyzed using profitability analysis and the Garret Ranking technique. Chicks up to the age  of eight weeks killed by predators such as dogs and cats were the major constraint faced by the poultry farmers. The beneficiaries’  second major constraint was a lack of knowledge about the scientific rearing of chickens. Labour cost was the highest of the total cost  of production. Income from selling eggs followed by selling males for meat purposes were major contributors to income generation.  Triple-cross chicken’s net income per unit of 22 birds was Rs. 8617.12, while indigenous chicken’s net income per unit was Rs. 6308.33.  BC ratio of triple cross chicken (2.58) was higher than BC ratio of indigenous chicken (2.20).
Keywords: Backyard poultry farming; Indigenous chicken; Profitability analysis; Triple-cross chicken